Gestión administrativa de la Cooperativa de Transporte de Pasajeros en Taxis Cachari en el período 2022. - Cando Orta, Nayeli Melisa (2023)
The present Case study was carried out in the CACHARI TAXIS PASSENGER TRANSPORT COOPERATIVE IN THE PERIOD 2022, which is dedicated to providing taxi transportation services to satisfy the mobility needs of users in the Babahoyo Canton, Province of Los Ríos. It is important to highlight that urban transport companies play a significant role in society, similar to that of industrial or commercial companies. In this study, the administrative management of the CACHARI TAXIS PASSENGER TRANSPORT COOPERATIVE was evaluated through the use of surveys. The objective was to understand their financial situation to make appropriate decisions. The tools used in this research guarantee efficient execution of administrative processes, facilitating the work of staff. In addition, proposals are presented to improve the growth and productivity of the cooperative in a competitive environment. A diagnosis of the current situation of the organization was carried out both internally and externally in the transportation market within the city. It is essential to highlight that a sustainable business involves not only meeting customer needs without harming the environment, but also operating in a socially responsible manner.